Artificial intelligence: A new tool in surgeon's hand - Amit Gupta; Tanuj Singla; Jaine John Chennatt; Lena Elizabath David; Shaik Sameer Ahmed; Deepak Rajput (Wolters Kluwer Medknow Publications, 2022)
Artificial intelligence (AI) is the future of surgery. Technological advancements are taking place at an incredible pace, largely due to AI or AI-backed systems. It is likely that there will be a massive explosion or "Cambrian explosion" of AI in our everyday life, largely aided by increased funding and resources spent on research and development. AI has also significantly revolutionized the medical field. The concept of machine learning and deep learning in AI is the crux of its success. In surgical practice, AI has numerous applications in the diagnosis of disease, preoperative planning, intraoperative assistance, surgical training and assessment, and robotics. The potential automation of surgery is also a possibility in the next few decades. However, at present, augmentation rather than automation should be the priority. In spite of the allure of AI, it comes with its own price. A robot lacks the "sixth sense" or intuition that is crucial in the practice of surgery and medicine. Empathy and human touch are also inimitable characteristics that cannot be replaced by an AI system. Other limitations include the financial burden and the feasibility of using such technology on a wide scale. Ethical and legal dilemmas such as those involving privacy laws are other issues that should be taken under consideration. Despite all these limitations, with the way technology is progressing, it is inevitable that AI and automation will completely change the way we practice surgery in the near future. Thus, this narrative review article aims to highlight the various applications and pitfalls of AI in the field of surgery.